Mammalian Target of Rapamycin Inhibitors and Wound Healing Complications in Kidney Transplantation: Old Myths and New Realities - Muhammad Abdul Mabood Khalil; Saeed M. G Al-Ghamdi; Ubaidullah Shaik Dawood; Said Sayed Ahmed Khamis; Hideki Ishida; Vui Heng Chong; Jackson Tan (Journal of Transplantation, 2022)
Mammalian target of rapamycin inhibitors (mTOR-I) lacks nephrotoxicity, has antineoplastic effects, and reduces viral infections in kidney transplant recipients. Earlier studies reported a significant incidence of wound healing complications and lymphocele. This resulted in the uncomfortable willingness of transplant clinicians to use these agents in the immediate posttransplant period. As evidence and experience evolved over time, much useful information became available about the optimal use of these agents. Understandably, mTOR-I effects wound healing through their antiproliferative properties. However, there are a lot of other immunological and nonimmunological factors which can also contribute to wound healing complications. These risk factors include obesity, uremia, increasing age, diabetes, smoking, alcoholism, and protein-energy malnutrition. Except for age, the rest of all these risk factors are modifiable. At the same time, mycophenolic acid derivatives, steroids, and antithymocyte globulin (ATG) have also been implicated in wound healing complications. A lot has been learnt about the optimal dose of mTOR-I and their trough levels, its combinations with other immunosuppressive medications, and patients’ profile, enabling clinicians to use these agents appropriately for maximum benefits. Recent randomized control trials have further increased the confidence of clinicians to use these agents in immediate posttransplant periods.